Factores que influyen en la Informalidad Tributaria de los productores de arroz y molinos en la provincia de San Martín año 2014 - Pezo Rodríguez, Sandy Mery (2015)
This research has the overall objective to identify the factors that directly affect the tax informality of rice producers and mills in the province of San Martin 2014 period are; her an applied and descriptive research was conducted and the deductive method was used because general data were analyzed, and then conclude on premises that are true to our research. We worked with a sample of 83 producers of rice and 7 mills in the province of San Martin, at which the results of our research show that the main factors influencing the tax informality of them are economic factors; poor tax culture; poor control of regulatory agencies, excessive tax burdens; unfair competition, because according to the survey of our above shows, 93% of rice farmers considered to be formal means reducing their profits; 84% of them are unaware of their tax obligations and stated that they had received talk or some guidance from SUNAT therefore have no tax culture; Furthermore 57% of respondents believe that SUNAT mills is not properly performing its audit work and in recent years has not had much presence in terms of enforcement of tax obligations applicable to this activity, they they consider that unfair competition is the reason that the milling companies not formalize the business of selling milled rice, preferring to do it clandestinely, since it allows them to gain more customers; 83% of rice farmers indicated that the rates applicable to this activity are very high and there should be a special rate for this type of activity.